Design of Spatial Adaptive Fingered Gripper Using Spherical Five-Bar Mechanism - Kim, Tae-Uk; Oh, Yonghwan (2014 INTERNATIONAL CONFERENCE ON ADVANCED MECHATRONIC SYSTEMS (ICAMECHS), 2014)
This paper suggests a design of a novel gripper using spatial adaptive fingers. The proposed gripper has spatial structure. Unlike the typical linkage-based under-actuated hands which only operate in a plane, the new gripper can perform motions in a plane and in space. In addition, the gripper can also perform non-prehensile movements, which cannot be realized in previous linkage systems due to the structure of input actuator. The core idea in the design of the finger is inspired from the Metacarpophalangeal(MCP) joint of human hand using a spherical five-bar linkage mechanism. The prototype of the proposed gripper is developed grasping tests with several different objects are also performed.